Opensid: Memberdayakan Perangakat Desa Tidu Di Kecamatan Pohjentrek, Kabupaten Pasuruan Dengan Sistem Informasi - Muhammad Udin; Khoirul Anwar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The application of technology in public services has become an indispensable obligation, even for the Village Government of Tidu in Pohjentrek Subdistrict, Pasuruan Regency. Manual approaches in public services are vulnerable to serious problems, such as the risk of losing important documents and the lack of structured recording of documents issued by the Village Government of Tidu. In response to this challenge, a community service effort was undertaken to support the Government and the community of Tidu Village in utilizing the Tidu Village Information Website. The mentoring and training sessions conducted successfully demonstrated that the implementation of the service system by the Village Government of Tidu is much more productive, with time savings and a transition from manual data management to digital format through the village information system.